2012
DOI: 10.5301/jva.5000125
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-center, Dose-escalation Study of Human type I Pancreatic Elastase (PRT-201) Administered after Arteriovenous Fistula Creation

Abstract: PurposeTo explore the safety and efficacy of PRT-201.MethodsRandomized, double-blind, placebo-controlled, single-dose escalation study of PRT-201 (0.0033 to 9 mg) applied after arteriovenous fistula (AVF) creation. Participants were followed for one year. The primary outcome measure was safety. Efficacy measures were the proportion with intra-operative increases in AVF outflow vein diameter or blood flow ≥25% (primary), changes in outflow vein diameter and blood flow, AVF maturation and lumen stenosis by ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…These early-phase studies of this drug to date have demonstrated safety and feasibility and have shown promising results with regard to patency outcomes (77)(78)(79). Given the promising results from early phase studies, an ongoing phase III randomized controlled clinical trial is evaluating perivascularly delivered elastase administered at the time of new radiocephalic AVF creation (NCT02110901).…”
Section: Potential Future Molecular Targets That May Translate Into Tmentioning
confidence: 99%
“…These early-phase studies of this drug to date have demonstrated safety and feasibility and have shown promising results with regard to patency outcomes (77)(78)(79). Given the promising results from early phase studies, an ongoing phase III randomized controlled clinical trial is evaluating perivascularly delivered elastase administered at the time of new radiocephalic AVF creation (NCT02110901).…”
Section: Potential Future Molecular Targets That May Translate Into Tmentioning
confidence: 99%
“…Additionally, it is postulated that elastin fragments have chemotactic properties that could inhibit migration of myofibroblasts from the adventitial to the intima and thereby, inhibit neointimal hyperplasia. An early phase placebo-controlled, dose-escalation trial of human type I pancreatic elastase (NCT01305824) applied to the adventitial surface of the newly created AVFs found that the treatment was well tolerated (81). Larger trials of human type I pancreatic elastase for AVFs (NCT01305824) and AVGs (NCT01001351) have recently been completed, and the results are forthcoming.…”
Section: Perivascular Approachesmentioning
confidence: 99%
“…Two recent examples of perivascular-delivered therapies include (1) endothelial cell-loaded gel foam wraps and (2) recombinant elastase therapy. Both of these therapies have been tested in early-phase clinical trials and have shown safety and feasibility (50,51). A larger, multicenter, phase II study of endothelial cell-loaded gel foam wraps will be initiated in the United States in 2013.…”
Section: Local Perivascular Delivery Therapiesmentioning
confidence: 99%